2022
DOI: 10.2196/27795
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Machine Learning–Based Decision Support System for Urinary Tract Infections: Prospective Observational Study in 36 Primary Care Practices

Abstract: Background There is increasing attention on machine learning (ML)-based clinical decision support systems (CDSS), but their added value and pitfalls are very rarely evaluated in clinical practice. We implemented a CDSS to aid general practitioners (GPs) in treating patients with urinary tract infections (UTIs), which are a significant health burden worldwide. Objective This study aims to prospectively assess the impact of this CDSS on treatment success … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Of the six included studies, three are from the United States [ 27 , 28 , 29 ], while the rest are from the Netherlands [ 30 ], Spain [ 31 ], and China [ 32 ]. The two most common study designs were randomized clinical trials (two) [ 27 , 29 ], one of which was single-blinded [ 27 ], and observational cross-sectional studies (two) [ 28 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the six included studies, three are from the United States [ 27 , 28 , 29 ], while the rest are from the Netherlands [ 30 ], Spain [ 31 ], and China [ 32 ]. The two most common study designs were randomized clinical trials (two) [ 27 , 29 ], one of which was single-blinded [ 27 ], and observational cross-sectional studies (two) [ 28 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…All six studies were performed in primary care clinics. The number of clinicians using the CDSSs was reported in four studies [ 28 , 29 , 31 , 32 ], and the number of patients assessed was reported in three studies [ 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accuracy was most commonly measured, although a few studies examined safety and clinician time (e.g., [44,46,53]). Effects on care-delivery were assessed using a variety of measures including time to treatment (e.g., [29,39,67,68]). Patient outcomes were assessed using measures like length of stay and mortality (e.g., [61,62,66]), but no studies examined adverse events due to AI errors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported strategies to incorporate well-known considerations for the use of digital health technologies such as ensuring that AI advice was actionable (e.g., when algorithms were designed to operationalise national guidelines [48]), and integrated into clinical workflow and existing CISs including EHRs (e.g., [22,29,77]). In one study where the AI was not integrated into the EHRs, general practitioners needed to enter patient characteristics into a web-based version of the AI [68]. A key challenge for system implementation is to build upon general considerations for digital health and identify specific measures required for the safe and effective use of ML algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation